Adalimumab‐induced platelet antibodies resulting in severe thrombocytopenia. Issue 9 (8th March 2021) - Boiten, Henk‐Jan; Amini, Sufia; Wolfhagen, Frank H. J.; Westerweel, Peter E.
Abstract : Anti‐tumour necrosis factor‐α (TNFα) agents are effective in diseases including Crohn's disease but may cause cytopenias. The mechanisms involved in anti‐TNFα agent‐induced thrombocytopenia are scarce. We report a 73‐year‐old male with Crohn's disease for which he currently used adalimumab, an anti‐TNFα agent. He had received mesalazine and infliximab before the treatment of adalimumab. No comorbidities were present. Routine laboratory tests revealed a deep thrombocytopenia (thrombocytes 24 × 10 9 /L), after which adalimumab was discontinued. Bleeding symptoms included cutaneous haematomas and mild epistaxis. Direct monoclonal antibody‐specific immobilization of platelet antigens revealed autoantibodies specific to glycoprotein IIb/IIIa and glycoprotein V platelet receptors. There was no bone marrow suppression. Other causes of the thrombocytopenia were ruled out. The platelet count normalized after adalimumab discontinuation. No further interventions were required. Monitoring thrombocyte levels after initiating anti‐TNFα agents is recommended, which could lead to prevention of this potentially fatal phenomenon.